Efficacy of Distal Pancreatectomy Combined With Modified DuVal Procedure in Patients With a High Risk of Postoperative Pancreatic Fistula. Issue 6 (June 2022) - Mori, Yasuhisa; Nakata, Kohei; Ideno, Noboru; Ikenaga, Naoki; Okabe, Yasuhiro; Nakamura, Masafumi
Background: The incidence of postoperative pancreatic fistula (POPF) after distal pancreatectomy (DP) remains high. The present study aimed to clarify the efficacy of our modified DuVal (mDuVal) pancreatojejunostomy following DP in patients with a high risk of POPF. Methods: The medical records of 346 consecutive patients who underwent DP between 2006 and 2016 were retrospectively reviewed. Perioperative features were compared between 24 patients undergoing mDuVal (mDuVal group) and 322 patients undergoing standard DP (standard DP group). Results: Preoperative American Society of Anesthesiologists physical status 1 was more frequent in the standard group than in the mDuVal group ( P = .02). The start of a solid diet after operation was significantly earlier in the mDuVal group than in the standard DP group ( P = .01), while there were no significant differences between the groups for clinically relevant POPF, amylase concentration in the drainage fluid on postoperative day 1 and days 3-5, time to drain removal, additional intervention for POPF, overall complications, or postoperative hospital stay. Discussion: The mDuVal procedure could be an option for patients with a high risk of POPF to improve the outcomes after DP. Further investigation involving large study populations is necessary to clarify the efficacy of this procedure.